Work-from-home influence on the commercial office demand: Evidence from Klang valley after the pandemic - Liew, Pei Zhi (2023)
The challenge of surviving in a highly competitive office market has become evengreater as the Klang Valley now faces an overwhelming amount of vacant commercial office space due to the continued decline in occupancy rates, alongwith work-from-home (WFH) emerging especially after the introduction of Covid- 19 pandemic. Thus the paradox situation trigger the need for this paper to identifythe main driver and main obstacle influencing the practice of work-from-home toward the commercial office demand. Moreover, this paper also to rank the function of commercial office space after the pandemic. The use of surveyquestionnaires for data collection is consistent with the chosen researchmethodology of a positivist and deductive approach with a quantitative researchdesign for this paper. The researcher used the SPSS statistical software andMicrosoft Excel for data analysis. There were 250 survey were distributed throughGoogle Form and only 103 survey is returned with valid answers. Next, these feedback comprise of 22 measurement variables within 5 different factors that helps further describe the research question. In the end, the main driver influencingthe practice of work-from-home toward the commercial office demand which has concluded in this paper is home office design factor. This paper reported that the improvement in home design associated with the emerging of home office awareness, such as a dual key concept where a unit for family-living purpose while another unit for workplace purpose, or dedicated room for office use in a residential property, has created a stronger driver on influencing work-from-home practice affect the commercial office demand in Klang Valley. Another key fact toremember is, the job characteristics factor is the main obstacle thereby. The higher substantial of the concentration work (i.e. heavy paper work) for a commercial office space user, the poorer of the obstacle force he facing in response to the work-from-home practice, could possibly reduce the demand toward the physical commercial office. Lastly, the commercial office space after the pandemic will be transform as the privileged site for (1) brainstorming and collaborative activities, (2) new hires on boarding, and (3) talent development, rather than the sole place where intend to (4) increasing productivity, (5) building community forming, and(6) use as meeting space.